2020
DOI: 10.1002/ejoc.201901704
|View full text |Cite
|
Sign up to set email alerts
|

Production of γ‐Valerolactone from One‐Pot Transformation of Biomass‐Derived Carbohydrates Over Chitosan‐Supported Ruthenium Catalyst Combined with Zeolite ZSM‐5

Abstract: It remains as a challenge to directly transform the biomass‐derived C5 carbohydrates, such as furfural (FF) and its upstream product xylose and hemicellulose, to γ‐valerolactone (GVL), a versatile renewable chemical platform, due to various restrictions in the current synthetic strategies. Using formic acid as green hydrogen source, we synthesized the recyclable chitosan‐Ru/PPh3 catalyst system, effective for both the hydrogenation of FF to furfuryl alcohol (FAL) and the reduction of levulinic acid (LA) or eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 82 publications
1
14
0
Order By: Relevance
“…However, when alcohol is the H-donor, it goes through a dehydrogenation to produce hydrogen atoms, and the byproducts are an aldehyde or a ketone (ROH to RO in Fig. 2), (Wang et al 2020b). The regeneration of the solvent can restore it, as in the case of alcohol (Geboers et al 2014), which can be reused (Fig.…”
Section: Gamma-valerolactone From Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when alcohol is the H-donor, it goes through a dehydrogenation to produce hydrogen atoms, and the byproducts are an aldehyde or a ketone (ROH to RO in Fig. 2), (Wang et al 2020b). The regeneration of the solvent can restore it, as in the case of alcohol (Geboers et al 2014), which can be reused (Fig.…”
Section: Gamma-valerolactone From Biomassmentioning
confidence: 99%
“…3). Hydrogenation is exothermic and depends on the catalyst activity, whereas cyclization is endothermic (Wang et al 2020b). The C-H formation in the γ-carbon to form the alkoxy intermediate is rate-controlling (Mamun et al 2019), whereas the ring closure is easy (Chia and Dumesic 2011;Mamun et al 2019).…”
Section: Gamma-valerolactone From Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid perovskites have recently emerged as promising photovoltaic materials for approaching efficient perovskite solar cells (PSCs) [1][2][3][4] and ultrasensitive perovskite photodetectors (PPDs) [5][6][7] due to the low exciton binding energy, long charge carrier diffusion length and high charge carrier mobility of perovskite materials, and the possibility of cost-effective high-throughput manufacturing of perovskite photovoltaics. [8][9][10][11][12][13][14][15][16] An impressive device performance has been reported from the state-of-the-art device architectures through morphological manipulation and generic interface engineering. [17][18][19][20][21][22][23][24] Studies indicated that the defect-assisted charge carrier recombination in perovskite photoactive layer was one of issues needs to be resolved for further boosting device performance.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Studies indicated that the defect-assisted charge carrier recombination in perovskite photoactive layer was one of issues needs to be resolved for further boosting device performance. [8][9][10][11][12][13][14][15][16] Utilization of Lewis acid and/or Lewis base to passivate the surface-defect has been attempted to address above issues, and boosted device performance was indeed observed from perovskite photovoltaics. [25][26][27] Magnetic nanoparticles (MNPs) and external magnetic field (EMF) have been applied for enhancing electroluminescence and photoluminescence efficiencies, and photocurrent in optoelectronics.…”
Section: Introductionmentioning
confidence: 99%